PENGEMBANGAN MODUL BERBASIS POE (PREDICT, OBSERVE, EXPLAIN) MATERI USAHA DAN ENERGI DITINJAU DARI KEMAMPUAN KOGNITIF - Aria Tanti Wika Sari; Dedy Hidayatullah Alarifin (Jurnal Pendidikan Fisika, 2016)
Physics to prepare the student to be able to encounter of changes in life. Because it, the student must have an interesting module for students to learn independently at home. One of the model learning is potential of students to solve problems practice is POE. This research is a R&D with the procedural model that "4-D models. This model consists of four stages of development, there are define, design, development and dissemination. The results of this research is the quality of the modules physics-based POE according to subject matter experts, media specialists, and linguists have eligibility criteria are very decent with their respective ideals percentage of 80,20%, 80,30%, and 81,25%, and the effectiveness of the module-based POE (Predict, Observe, Explain) in terms of the cognitive abilities of the students got high criterion with an overall .